Evaluation of Platelet and Leukocyte Counts in Canine Platelet-Rich Plasma Obtained After Successive Blood Collections From the Same Patient and the Effects of Freezing on the Concentration of Growth Factors Present in It - DeMello, Victoria; Chen, Grace; Wakshlag, Joseph; Mason, David (Frontiers in Veterinary Science, 2022)
Abstract: Objective: The purpose of this study was two-fold: to evaluate whether the timing of collection influences the platelet concentration and leukocyte counts of PRP samples, and to evaluate consistency in growth factor concentrations in canine PRP over time after freezing and storage without a preservation agent for 6 months of time. MATERIALS & METHODS: Whole blood collection was performed four times over the course of four weeks. All PRP samples were evaluated with a CBC analysis and then stored. The PRP samples were frozen and stored without a preservation agent using a -20º C freezer for the duration of the 4-week study. RESULTS: The platelet and leukocyte concentrations were not statistically significant between the timing of blood draws over the course of 4 weeks. All three growth factors were present in measurable quantities. Clinical Relevance: PDGF, TGF, and VEGF were all present in measurable quantities. Furthermore, PDGF and TGF were correlated with platelet concentration of the final PRP. VEGF concentrations were able to be quantified. We correctly hypothesized growth factor concentrations would be present and measurable in canine PRP frozen and stored without a preservation agent for 6 months.